Managing Bipolar Disorder in Clinical Practice - Vieta, Eduard; SpringerLink (Online service) (Tarporley : Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2013)
Written by Eduard Vieta, a world renowned award winning expert in this field, Managing Bipolar Disorder in Clinical Practice, Third Edition, is an up-to-date, concise practical handbook developed with the clinician in mind. Including the most recent clinical guidelines, including the British Association for Psychopharmacology (BAP) and Canadian Network for Mood and Anxiety Treatments (CANMAT) guidelines, this handbook is intended to highlight every major aspect of this serious mental health disorder, including assessment, treatment, long-term management, and recent developments.
Overview of bipolar disorder -- Psychosocial consequences -- Etiology and disease course -- Assessment and diagnosis -- Suicide risk -- Overview of management options -- Pharmacological management of depressive episodes -- Pharmacological management of manic episodes -- Treatment-resistant bipolar disorder -- Psychosocial interventions.
Keywords: Medicine; Family medicine; Emergency medicine; Psychiatry; Psychopharmacology; Psychotherapy; Behavioral Therapy; Medicine & Public Health; Psychiatry; Psychopharmacology; Behavioral Therapy; Primary Care Medicine; General Practice / Family Medicine; Psychotherapy